Clinical analysis on surgical management of type III external auditory canal cholesteatoma: a report of 12 cases. (2nd October 2016) - Yan, Yan; Dong, Siqi; Hao, Qingqing; Liu, Riyuan; Xu, Guangyu; Zhao, Hui; Yang, Shiming
Abstract: Objective: To investigate surgical management of type III EACC with lesions involving the posterior external auditory canal and mastoid. Methods: This retrospective case review was conducted in 12 patients with type III EACC who underwent intact canal wall mastoidectomy with tympanoplasty and canal wall reconstruction with autologous cortical bone. Results: During the follow-up, all patients obtained successful results on external auditory canal structures and hearing improvement, except for one patient who needed a revision operation for the fistula between the reconstructed wall and the mastoid. Conclusion: Intact canal wall mastoidectomy with tympanoplasty and canal wall reconstruction with autologous cortical bone was proved to be an effective and inexpensive choice for the patients with type III external auditory canal cholesteatoma (EACC) to achieve optimal outcomes.